Impact of food- related personality traits and behavioural determinants on buying intent of tourist towards local food of Uttarakhand - Chamoli, Abhay; Verma, Shiv Mohan; Rana, Vinay (Journal of Postharvest Technology, 2021)
There is a greater focus on comprehending the buyer's motivation for choosing different foods. The consumer food-related personality traits  are believed to be of great importance in influencing individual buying intention. The study is aimed at researching the tourist buying intention  towards local food in the state of Uttarakhand, by applying multiple regression techniques as methodology. The findings facilitate the  application of Ajzen's, Theory of Planned Behavior (TPB) to clarify the behavior patterns of the tourists’ intent towards local food. Besides, the  results indicate that Attitude, Subjective Norm, and Food-Related Personality Traits of food Neophobia/ Neophilia have a strong impact on the  tourist buying intention towards local food. However, the impact of Perceived Behavioral Control (PBC) was insignificant after the evaluation of  the results. Based on statistical findings and results, a few recommendations have been proposed to the establishments involved in facilitating  the expansion plans of the local food sector of Uttarakhand.
Keywords: Local food,; perceived behavioral control (PBC),; food neophobia; theory of planned behavior